Views of Teachers Regarding Course Contents of Anatomy in Post Graduate MD Internal Medicine Curriculum (Bangladesh Journal of Anatomy, 2009)
Context: Anatomy is a compulsory subject for postgraduate medical courses of Bangladesh. MD internal medicine is a clinical course run by different universities of Bangladesh. To maintain a standard of medical education a curriculum is essential for a course. Again course content is an essential part of a curriculum. Doctor of Medicine (MD) courses consist of three parts. In Part-I, students study the basic medical subjects for six months. To produce clinicians with appropriate anatomical knowledge in a short time within six months period proper customized (relevant) course content regarding Anatomy part is necessary. But the problem is that in our postgraduate course much subjectivity is present in every aspects of curriculum. This subjectivity is due to inclusion of more general aspects of Anatomy and exclusion of specific deeper relevant Anatomy. Realizing this problem the present study was designed to formulate some principles for selecting course contents for the Anatomy portion of MD Internal Medicine course. Study Design: This was a descriptive study. Place & Period of study: Center for Medical Education, Dhaka from July 2007-June 2008. Method: It was based on analyses of opinion of students and teachers through focus group discussion involving teachers of Internal Medicine and Anatomy. These people were chosen through two stage random sampling within clusters. Two Focus group discussions were used to get feedback on the importance of various anatomical topics that should be included as course content. Of a total of 18 teachers response in focus group discussion. In FGD 83% response was received from the teachers in Anatomy and 66 % on teachers in Medicine. Result: Opinion derived from the FGD indicate that for the selection of the course content following concluding remarks should be made:• Cardiovascular anatomy, respiratory anatomy and anatomy of the nervous system should be considered important for the Internal Medicine. • For knowing the anatomical landmarks all of the surface anatomy should receive attention for Medicine. • Functional implication and effect of obliteration of arterial supply, lymphatic drainage and nerve supply receives importance. • Sectional and radiological anatomy is considered important for the course for interpretation of X-ray, CT scan and MRI. • Anatomical variation should be considered important as well as congenital anomalies of cardiovascular and genitourinary system. • Knowledge of the structure of the mucous membrane is important for clinical correlation of the biopsy reports. • Basic genetics, cell biology should be important but kept in mind that repetition should be avoided in others subjects as in Biochemistry and Physiology. Key words: Anatomy, Course content, MD Internal medicine.   doi: 10.3329/bja.v7i1.3027 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 55-61